Microwave assisted demulsification of water-in-crude oil emulsions - Zulkifly, Jemaat; Rosli , Mohd Yunus; Hafiz, Azura Hamza; Adnan, Ripin; Rohaida, Che Man; Mazura, Jusoh (Penerbit Universiti Sains Malaysia, 2004)
Emulsions are of considerable practical significance both in processing industry and in the consumer sector. In the petroleum industry emulsions phenomena are particularly aware because it can lead to upstream and downstream production upset. A recent report stated that about 80% of exploited crude oil exists in an emulsion state, all over the world (Xia et al., 2004).